Replanting of first‐cycle oil palm results in a second wave of biodiversity loss. Issue 11 (7th May 2019) - Ashton‐Butt, Adham; Willcock, Simon; Purnomo, Dedi; Suhardi,; Aryawan, Anak A. K.; Wahyuningsih, Resti; Naim, Mohammad; Poppy, Guy M.; Caliman, Jean‐Pierre; Peh, Kelvin S.‐H.; Snaddon, Jake L.
Abstract: Conversion of forest to oil palm plantations results in a significant loss of biodiversity. Despite this, first‐cycle oil palm plantations can sustain relatively high biodiversity compared to other crops. However, the long‐term effects of oil palm agriculture on flora and fauna are unknown. Oil palm has a 25‐year commercial lifespan before it must be replanted, due to reduced productivity and difficulty of harvesting. Loss of the complex vegetation structure of oil palm plantations during the replanting process will likely have impacts on the ecosystem at a local and landscape scale. However, the effect of replanting on biodiversity is poorly understood. Here, we investigate the effects of replanting oil palm on soil macrofauna communities. We assessed ordinal richness, abundance, and community composition of soil macrofauna in first‐ (25‐ to 27‐year‐old) and second‐cycle oil palm (freshly cleared, 1‐year‐old, 3‐year‐old, and 7‐year‐old mature). Macrofauna abundance and richness drastically declined immediately after replanting. Macrofauna richness showed some recovery 7 years after replanting, but was still 19% lower than first‐cycle oil palm. Macrofauna abundance recovered to similar levels to that of first‐cycle oil palm plantations, 1 year after replanting. This was mainly due to high ant abundance, possibly due to the increased understory vegetation as herbicides are not used at this age. However, there were subsequent declines in macrofauna abundance 3 and 7 years after replanting, resulting in a 59% drop in macrofauna abundance compared to first‐cycle levels. Furthermore, soil macrofauna community composition in all ages of second‐cycle oil palm was different to first‐cycle plantations, with decomposers suffering particular declines. After considerable biodiversity loss due to forest conversion for oil palm, belowground invertebrate communities suffer a second wave of biodiversity loss due to replanting. This is likely to have serious implications for soil invertebrate diversity and agricultural sustainability in oil palm landscapes, due to the vital ecosystem functions that soil macrofauna provide. Abstract : This study explores the effect of replanting oil palm on belowground biodiversity. It finds that replanting causes a decline in invertebrate diversity, abundance and alters community composition. This could have serious impacts on soil sustainability and conservation of belowground diversity.